Baldness, acne and testicular germ cell tumors - Trabert, Britton (2010)
Androgen levels during critical periods of testicular development may be involved in the etiology of testicular germ cell tumors (TGCT). We evaluated the roles of adolescent and early adult life correlates of androgen exposure and TGCT in a hospital-based case control study. TGCT cases (n=187) and controls (n=148), matched on age, race and state of residence, participated in the study. Unconditional logistic regression was used to estimate associations between TGCT and male pattern baldness, severe acne, markers of puberty onset and body size. Cases were significantly less likely to report hair loss than controls (OR, 0.6; 95% CI, 0.4, 1.0). Amount of hair loss, increasing age at onset and increasing rate of loss were all inversely associated with TGCT (rate of hair loss: p-trend=0.03; age at onset: p-trend=0.03; amount of hair loss: p-trend=0.01). History of severe acne was inversely associated with TGCT (OR, 0.5; 95% CI, 0.3, 0.9) and height was positively associated with TGCT (p-trend=0.02). Increased endogenous androgen levels during puberty and early adulthood may be associated with decreased risk of TGCT. Additional studies of endogenous hormone levels during puberty and early adult life are warranted, especially studies evaluating the role of androgen synthesis, metabolism and uptake.